If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4w + -15 = 3w + -12 Reorder the terms: -15 + 4w = 3w + -12 Reorder the terms: -15 + 4w = -12 + 3w Solving -15 + 4w = -12 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. -15 + 4w + -3w = -12 + 3w + -3w Combine like terms: 4w + -3w = 1w -15 + 1w = -12 + 3w + -3w Combine like terms: 3w + -3w = 0 -15 + 1w = -12 + 0 -15 + 1w = -12 Add '15' to each side of the equation. -15 + 15 + 1w = -12 + 15 Combine like terms: -15 + 15 = 0 0 + 1w = -12 + 15 1w = -12 + 15 Combine like terms: -12 + 15 = 3 1w = 3 Divide each side by '1'. w = 3 Simplifying w = 3
| -23-4=-96 | | 5x^4y^2(-2x^2y)= | | -8b+1=3b+6(3b+5) | | 1+x/4=-1 | | 22.7-4.6f=(-8.58) | | -18(10+3k)=16(k+15) | | 15x-2=3x | | 3s-13=2 | | 2x-8x-x=2+-16 | | 14w+(15)6=15w-5 | | 3(2x+3)=60 | | -1+x/4=0 | | 8w=4w | | 4x-b+6=b(2) | | 20x^2-5x=0 | | 19x+10=4(3x+3)+7x-2 | | 2(4x-7)=12 | | -7(3+2x)+9=-68 | | 42+c=-9 | | 35t=50t-.75 | | (8/5)x+x=273 | | 4x^3y^3*x^0y^3= | | 35x^2+44x-7=0 | | (3x+10)=(5x-10) | | 16+.3x=3x | | 15=n-22 | | 96=-24s | | 5y+3(y-7)=5(y+1)-4 | | 35=z-15 | | 14k+4=6k+14 | | 15=(2x-10)/2 | | 7m+18m=28+11m |